2018
DOI: 10.1016/j.euromechflu.2018.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation on three-dimensional shock train structures in rectangular isolators

Abstract: The understanding of the formation of shock trains in high-speed engines is vital for the improvement of engine design. The formation of these flow structures in a narrow duct, driven by the presence of the viscous effects on the walls, is an extremely complex process that is not fully understood. This investigation demonstrates the high sensitivity of the shock train to the solving equations. The establishment of the shock train in the duct mainly depends on the way that the boundary layer develops on the wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Here too, their results agree with the experimental results (Sun et al 2003). Gnani et al (Gnani et al 2018b;Gnani et al 2018a) investigated shock train characteristics and their movements under forced back pressure oscillation using 2-dimensional RANS with a k-ω model. Upon using various turbulence models he concluded that the k-ω Wilcox model compares more favorably with the experimental results (Sun et al 2003).…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Here too, their results agree with the experimental results (Sun et al 2003). Gnani et al (Gnani et al 2018b;Gnani et al 2018a) investigated shock train characteristics and their movements under forced back pressure oscillation using 2-dimensional RANS with a k-ω model. Upon using various turbulence models he concluded that the k-ω Wilcox model compares more favorably with the experimental results (Sun et al 2003).…”
Section: Introductionsupporting
confidence: 85%
“…In the present work, an attempt has been made to understand the effect of back pressure, inflow Mach number and divergent angle on the characteristics of the shock train. Though the flow is three dimensional in nature, the center of the duct is assumed to be two-dimensional where the side wall does not influence the main flow field across the shock train (Gnani et al 2018b). In a separate investigation, Section 3.4 shows the effect of side wall on the shock train.…”
Section: Resultsmentioning
confidence: 99%
“…Even though the real flow is 3 dimensional, the center of the duct can be assumed to be two-dimensional where the sidewall does not interfere with the core flow. 32 In the present work, an attempt has been made to control the shock train in the isolator by partial removal of the upstream boundary layer. The effect of upstream to downstream pressure ratio on the location of shock train and the influence of boundary layer suction on shock train is studied.…”
Section: Resultsmentioning
confidence: 99%
“…Conventional schlieren techniques [12,13] have been limited to use only for qualitative visualisation of the flow fields inside a shock train since it requires a cumbersome process to extract the two-dimensional density field from schlieren images. For validation purpose of the computational scheme, these experimentally measured schlieren images are often compared with the simulated ones [14][15][16][17][18]. Due to difficulty of obtaining the quantitative information of the flow fields inside the shock train, it is often seen that the measured wall pressure distribution is used for validation of the computational methodology [16,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…For validation purpose of the computational scheme, these experimentally measured schlieren images are often compared with the simulated ones [14][15][16][17][18]. Due to difficulty of obtaining the quantitative information of the flow fields inside the shock train, it is often seen that the measured wall pressure distribution is used for validation of the computational methodology [16,[18][19][20]. It is worth mentioning that although a good agreement between the measured and simulated wall pressure distributions or schlieren images can be achieved, the computed scalar quantities or vector fields inside the shock train could be still inaccurate.…”
Section: Introductionmentioning
confidence: 99%